Evaluation of Fusarium Head Blight Resistance in 410 Chinese Wheat Cultivars Selected for Their Climate Conditions and Ecological Niche Using Natural Infection Across Three Distinct Experimental Sites - Yan, Zhen; Chen, Wanquan; van der Lee, Theo; Waalwijk, Cees; van Diepeningen, Anne D.; Feng, Jie; Zhang, Hao; Liu, Taiguo (Frontiers in Plant Science, 2022)
Exploiting wheat cultivars with stable resistance to Fusarium Head blight (FHB) and toxin accumulation is a cost-effective and environmentally friendly strategy to reduce the risk of yield losses and contamination with mycotoxins. To facilitate the deployment of stable cultivar resistance, we evaluated FHB resistance and resistance to mycotoxin accumulation in 410 wheat lines bred by local breeders from four major wheat growing regions in China after natural infection at three distinct locations (Hefei, Yangzhou and Nanping). Significant differences in disease index were observed among the three locations. The disease indexes (DI’s) in Nanping were the highest, followed by Yangzhou and Hefei. The distribution of DI’s in Yangzhou showed the best discrimination of FHB resistance in cultivars. Growing region and cultivar had significant effect on DI and mycotoxins. Among the climate factors, relative humidity and rainfall were the key factors resulting in the severe disease. Even though most cultivars were still susceptible to FHB under the strongly conducive conditions applied, the ratio of resistant lines increased in the Upper region of the Yangtze River (UYR) and the Middle and Lower Region of the Yangtze River (MLYR) between 2015 and 2019. Deoxynivalenol (DON) was the dominant mycotoxin found in Hefei and Yangzhou, while NIV was predominant in Nanping. Disease indexes were significantly correlated with DON content in wheat grain.